2013
DOI: 10.1371/journal.pone.0065767
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Agonist and Pharmacochaperone Properties of MK-0524 on the Prostanoid DP1 Receptor

Abstract: Prostaglandin D2 (PGD2) acts through two G protein-coupled receptors (GPCRs), the prostanoid DP receptor and CRTH2 also known as DP1 and DP2, respectively. Several previously characterized GPCR antagonists are now classified as inverse agonists and a number of GPCR ligands are known to display pharmacochaperone activity towards a given receptor. Here, we demonstrate that a DP1 specific antagonist, MK-0524 (also known as laropiprant), decreased basal levels of intracellular cAMP produced by DP1, a Gαs-coupled r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 97 publications
(118 reference statements)
1
14
0
Order By: Relevance
“…2D). We also investigated the effect of MK0524, a selective antagonist and inverse agonist at DP 33,34 . As previously also observed in a DSS model 11 , MK0524 (1 mg/kg) worsened inflammation scores in TNBS colitic mice by ~20%.…”
Section: Resultsmentioning
confidence: 99%
“…2D). We also investigated the effect of MK0524, a selective antagonist and inverse agonist at DP 33,34 . As previously also observed in a DSS model 11 , MK0524 (1 mg/kg) worsened inflammation scores in TNBS colitic mice by ~20%.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, PC stabilization of A1 adenosine receptor folding intermediates promotes the dissociation of the receptor from HSP 40 protein D1 receptor interacting protein 78 (DRiP78) [91]. Intriguingly, PCs promote the interaction of the prostanoid DP1 receptor and ANKRD13C [92], a cytoplasmically localized molecular chaperone for GPCRs that aids in forward trafficking [93]. …”
Section: Pcs Affect the Interaction Of Target Proteins With Molecumentioning
confidence: 99%
“…For nACh receptors, agonists are more potent PCs than antagonists, possibly because heteromeric assembly may occur more efficiently if the receptor is in an activated or desensitized state [72]. In addition to agonist PCs, inverse agonists PC have been identified for the prostanoid DP1 receptor [92]. Moreover, V2R antagonists are “protean agonists” serving as PCs for certain mutants while acting as inverse agonists at wild type receptors [111] further revealing the complexities of pharmacological chaperoning.…”
Section: Pharmacology Of Pcsmentioning
confidence: 99%
“…Our previous studies have shown that a large population of DP1 is retained in intracellular compartments after synthesis ( Parent et al, 2010 ; Labrecque et al, 2013 ). Furthermore, we reported that L-PGDS was localized to the ER and other intracellular compartments ( Mathurin et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%